Diretrizes norteadoras de programas e políticas públicas e formação continuada de professores dos anos iniciais do ensino fundamental para promover o letramento digital docente - Silva, Vilemar Martins da (2024)
Digital literacy represents not only the practices of reading and writing, in a digital context, but the use of digital technological resources in a conscious and critical way, handling, interpreting, managing, sharing and creating meaning in digital communication. This skill requires skills and techniques necessary for the use of digital information and communication technologies (DIT). This form of literacy is the result of the digital age and social practices that are part of current reality. This reality makes it essential that education incorporates this phenomenon into its teaching practice. Therefore, it is necessary to encourage practices that improve the use of technologies and their languages in education. Therefore, it is important that the continued training of teachers adapts to the new reality, rethinking theoretical studies and pedagogical strategies that incorporate digital literacy in the teaching and learning process. Thus, this study focused on teacher training and the contribution of digital literacy as a teaching policy for democratization and technological inclusion. In this sense, the general objective was to develop guidelines for the continued training of teachers in the initial years of elementary school, which promote the development of digital skills and abilities in a conscious and critical way. The study carried out was basic in nature and took place in three stages: data collection from participating subjects through questionnaires and semi-structured interviews; preparation and implementation of an extension course and, finally, the creation of a digital guide containing the guiding guidelines for teacher training programs and policies. The qualitative data of this study were analyzed with the help of the Content Analysis methodology (BARDIN, 2010). As an educational product, in addition to a course plan that could contribute to the inclusion of digital literacy in continuing education, guidelines were developed to define public policies for continuing teacher training, considering digital inclusion. The activities carried out during the course were supported by the Digital Educational Laboratory-LDE and the Virtual University Institute-IUVI, both from UFC, and had, as target audience, teachers from the initial years of municipal schools. For data collection, semi-structured interviews were carried out and questionnaires were applied on the subjects' previous and subsequent knowledge and perceptions. The research aims to contribute to educational development, emphasizing digital inclusion policies and teacher training, through a teaching methodology focused on digital literacy.